(untitled) (Global Journal of Management and Business Research, 2020)
Internet proposes services and tools which transform in depth the on-line transactions B-to-B. So, the electronic marketplaces are considered as a real revolution since about twenty years. The first objective of this article is to explain the process of two types of electronic reverse auctions organized in marketplaces. In the second part, we try to answer the question: Do electronic reverse auctions really optimize the supply chain after more than two decades of use? We will also try to show the interests of a global vision and not only on prices reduction in the process of these reverse auctions.